Therapeutic Potential and Pharmaceutical Development of Thymoquinone: A Multitargeted Molecule of Natural Origin - Goyal, Sameer N.; Prajapati, Chaitali P.; Gore, Prashant R.; Patil, Chandragouda R.; Mahajan, Umesh B.; Sharma, Charu; Talla, Sandhya P.; Ojha, Shreesh K. (Frontiers in Pharmacology, 2017)
Thymoquinone, a monoterpene molecule is chemically known as 2-methyl-5-isopropyl-1, 4-benzoquinone. It is abundantly present in seeds of Nigella sativa L. that is popularly known as black cumin or black seed and belongs to the family Ranunculaceae. A large number of studies have revealed that thymoquinone is the major active constituent in N. sativa oil this constituent is responsible for the majority of the pharmacological properties. The beneficial organoprotective activities of thymoquinone in experimental animal models of different human diseases are attributed to the potent anti-oxidant and anti-inflammatory properties. Thymoquinone has also been shown to alter numerous molecular and signaling pathways in many inflammatory and degenerative diseases including cancer. Thymoquinone has been reported to possess potent lipophilicity and limited bioavailability and exhibits light and heat sensitivity. Altogether, these physiochemical properties encumber the successful formulation for the delivery of drug in oral dosages form and restrict the pharmaceutical development. In recent past, many efforts were undertaken to improve the bioavailability for clinical usage by manipulating the physiochemical parameters. The present review aimed to provide insights regarding the physicochemical characteristics, pharmacokinetics and the methods to promote pharmaceutical development and endorse the clinical usage of TQ in future by overcoming the associated physiochemical obstacles. It also enumerates briefly the pharmacological and molecular targets of thymoquinone as well as the pharmacological properties in various diseases and the underlying molecular mechanism. Though, a convincing number of experimental studies are available but human studies are not available with thymoquinone despite of the long history of use of black cumin in different diseases. Thus, the clinical studies including pharmacokinetic studies and regulatory toxicity studies are required to encourage the clinical development of thymoquinone.